Governors Island : local, state, & federal governments play deal or no deal - Elias, Jaan; Barton-Sweeney, Alexandra; Oster, Sharon M.; Podolny, Joel M. (Joel Marc) ([London] : SAGE, 2016)
On a helicopter flight to a ceremony at the United Nations in 1995, President Clinton and New York's Senior Senator Daniel Patrick Moynihan flew across New York City's lower harbor. According to Moynihan, the helicopter swooped by a small ice-cream cone shaped island and 'Castle Williams, Fort Jay, the great lawns, the barracks - the McKim Mead & White barracks - all but leapt up at us. 'What is that?' asked the president. 'Governors Island, sir,' I said. The federal government had occupied it free of charge for on to two centuries. There was a one-dollar exchange in the 1920's. No matter. Mightn't we have it back?
Originally Published in: Elias, J., Barton-Sweeney, A., Oster, S., & Podolny, J. (2007). Governors Island: Local, State, & Federal Governments Play Deal or No Deal. 07-027. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Public administration -- United States -- Case studies; Governors Island (New York County, N.Y.) -- Case studies; United States -- Politics and government -- Case studies